Korelasi Hadist Imam Tirmidzi dan Pasal 1 UU No.7 Tahun 1984 dalam Menjawab Isu Hukum Kesetaraan Gender dan Hak di Indonesia - Nur Shena Hindriastusi; Tajul Arifin (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This article aims to analyze the correlation between Article 1 of Law No. 7 of 1984, which ratifies the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), and selected hadiths narrated by Imam Tirmidhi, especially in addressing issues of discrimination and gender injustice. Using a descriptive-analytical method and a normative juridical approach, this study relies on primary data sources such as national legislation and the Jami’ at-Tirmidhi hadith collection, as well as secondary data from relevant Islamic legal and scholarly literature. Data collection was conducted through literature review and analyzed qualitatively. The findings indicate that there are normative foundations and values within the hadiths that can be reinterpreted contextually and in line with maqashid al-shari’ah, supporting the principles of justice and gender equality as mandated in Indonesian positive law.